2015
DOI: 10.3998/ark.5550190.p009.324
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of new derivatives of 3,4-dihydropyrimidinone, and substituted imidazolin-2-ones

Abstract: Three-component condensation of arylglyoxals, acetylacetone and urea in EtOH in the presence of small amounts of HOAc gives rise to 5-acetyl-4-aroyl-6-methyl-3,4-dihydropyrimidinones or 5-aryl-1,3-dihydro-2H-imidazol-2-ones containing an acetylacetone fragment in position 4. (1H-Pyrazol-4-yl)-1,3-dihydro-2H-imidazol-2-one derivatives were obtained via the reaction of the latter compounds with hydrazine. Doubt is cast upon an earlier report of the formation of pyrimido-pyridazines by condensation of hydrazines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…For example, Wu et al reported the β-addition-cyclization reactions of triketone enones for the synthesis of polyfunctionalized furans 3 and other heterocycles. 4 Lu et al disclosed an elegant NUSIOC-Phos-catalyzed β-selective reaction cascade of triketone enones with substituted allenoates to prepare bicyclic acetal compounds. 5 In sharp contrast, the regio-reversed α-addition of triketone enones remains a daunting challenge and has, to the best of our knowledge, never been reported.…”
mentioning
confidence: 99%
“…For example, Wu et al reported the β-addition-cyclization reactions of triketone enones for the synthesis of polyfunctionalized furans 3 and other heterocycles. 4 Lu et al disclosed an elegant NUSIOC-Phos-catalyzed β-selective reaction cascade of triketone enones with substituted allenoates to prepare bicyclic acetal compounds. 5 In sharp contrast, the regio-reversed α-addition of triketone enones remains a daunting challenge and has, to the best of our knowledge, never been reported.…”
mentioning
confidence: 99%